The Legal Provisions of the Penalty Clause in Employment Contract - Manar Mohammad Alghamdi (International Journal of Law Research and Studies, 2025)
The topic of the penalty clause in employment contracts represents one of the most precise legal issues in labor law, due to the nature of that Law itself and the protective character it imposes, which distinguishes employment contracts from other types of contracts. Especially since its legal regulation in this specific context is nearly non-existent. This study aims to analyze the legal provisions governing the penalty clause in light of the scarcity of legal texts, through examining its concept, legal nature, legitimacy, and the regulatory controls governing it, in addition to addressing the legal consequences resulting from its breach. The analytical method was adopted, based on Saudi regulations such as the Civil Transactions Law and the Labor Law, along with reference to relevant judicial rulings. The study reached a number of findings, most notably: that the penalty clause in employment contracts possesses a “mixed” legal nature, combining its compensatory role for damage and its deterrent function, along with a protective character resulting from the nature of the employment contract. To achieve a balance between the rights of the employee and the interests of the employer, the study recommends explicitly codifying the detailed provisions of the penalty clause within the Labor Law, and amending Article (77) to set a minimum compensation amount that may not be undercut, so as to prevent employers from exploiting this legislative gap, particularly in cases where the employee is the breaching party.
Keywords: Penalty Clause; Employment Contract; Article 77; Protective Nature; Saudi Labor Law; Contractual Breach